Collecting evidence of FLEGT-VPA impacts: Côte d’Ivoire country report - Tsanga, R.; Goetghebuer, T.; Leszczynska, N.; Berrada, K.; Almeida, B.; Newbery, J.; Cerutti, P.O. (Center for International Forestry Research, 2022)
This Côte d’Ivoire report is part of a series of seven country level studies (Cameroon, Côte d’Ivoire, Ghana, Guyana, Honduras, Indonesia and Republic of Congo) which intend to gather qualitative and quantitative evidence of the impacts of the Forest Law Enforcement Governance and Trade – Voluntary Partnership Agreement (FLEGT-VPA) process to date. This initiative was financed by the European Union and results are placed within the global European Union-FLEGT (EU-FLEGT) Monitoring and Evaluation (M&E) indicator database. The analysis is structured along five key thematic areas (with indicators clustered into governance and institutional effectiveness, illegal logging, forest conditions, economic development, and livelihoods and poverty). The methodology used is designed to be replicable over time as well as applicable to other countries. Each country assessment provides a baseline for future studies in the same country, that would help to measure progress (or regress) between two points in time. More countries can also be added over time to increase the overall sample and help to derive lessons based on more evidence. By covering seven countries that are in different stages of the VPA process – from negotiation to implementation to issuance of FLEGT licences – findings allow for global lessons to be learned across different geographies and time. These lessons and global findings are presented in a separate synthesis report, which combines results to outline a bigger picture of VPA process impacts where possible.